Comparison of Anticonvulsant Effects of Combined Regimens of Gabapentin and Verapamil with their Individual Effects - Itefaq Hussain Qureshi; Shahbana Usman Simjee (Journal of Bahria University Medical and Dental College, 2016)
Objective: To evaluate and compare in-vivo anticonvulsant effects of combined regimens of gabapentin and verapamil with their individual effects on kindled model of epilepsy in mice. Materials and Methods: This experimental study was carried out in H.E.J. Research Institute of Chemistry, International Center for Chemical and Biological Sciences, University of Karachi, from May 2009 to July 2011.Gabapentin (GBP) and Verapamil (VP) were used as tested drugs both as combined regimens as well as individual drugs, Phenytoin was used as reference drug. Kindling was produced by repeated administration of Pentylenetetrazole in a dose of 50 mg/kg by subcutaneous route every 48 hours for 20 days. Three doses of Gabapentin from 100 mg/kg to 300 mg/kg and three doses of Verapamil from 10 mg/kg to 30 mg/kg in combination regimens and individual drugs were administered by intraperitoneal route. Phenytoin was administered by intraperitoneal route in a dose of 50 mg/kg. Gabapentin, Verapamil and Phenytoin were administered once daily, however, on the day of Pentylenetetrazole treatment, the tested and reference drugs were injected 40 minutes before injecting Pentylenetetrazole.The anticonvulsive effects of combined regimens of tested drugs were compared to their individual effects as well as to reference drug Phenytoin. Results:Combination regimens of GBP and VP demonstrated dose dependent anti- seizure effects up to 100%. The different doses of combined regimens of GBP and VP demonstrated anti-seizure effects which were superior to their individual effects. Conclusion:Combination regimens of gabapentin and verapamil showed synergistic effects which were superior to their individual effects on kindled model of epilepsy in mice.